COMPLIANCE WITH THE USE OF PERSONAL PROTECTIVE EQUIPMENT FOR HEALTH WORKERS TO MAINTAIN SAFETY AT WORK - Syamsiah, Syamsiah; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT According to data from the World Health Organization (WHO), nosocomial infections are the main cause of high numbers pain and death in the world. This infection causes 1.4 million deaths every day in the world, according to prevalence surveys carried out by WHO in 55 hospitals from 14 countries representing 4 WHO Regions (Europe, Middle East, Southeast Asia and Western Pacific) showed an average of 8.7% and Southeast Asia as many as 10% of hospital patients experienced nosocomial infections. The purpose of this article is to formulate the best solution to reduce work accidents by complying with the use of personal protective equipment. The author's goal is to meet the needs of courses on campus. In this study, researchers used a modified systematic literature review, modified PRISMA procedures, Preferred Reporting Items for Systematic Reviews, and Meta-Analysis. The researcher explains the results of the six articles reviewed and their discussion. The six articles reviewed were Lira et al. (2022), Fazila (2021), Cristopher et al. (2022), Keiron et al. (2022), Gionatan et al. (2022), and Intan et al. (2022). From the review and discussion, researchers concluded that compliance with using personal protective equipment is related to knowledge. To increase workers' knowledge about PPE, companies need to make K3 promotions in the form of posters containing information related to PPE and posted on information boards. Keywords: Compliance, personal protective equipment, nosocomial